UJI EFEKTIVITAS ISOLAT JAMUR ENTOMOPATOGEN Metarhizium anisopliae (Metsch.) Sorokin TERHADAP RAYAP TANAH PADA PENGUJIAN DI LABORATORIUM DAN LAPANGAN - Agus Ismanto; Paimin Sukartana (BRIN Publishing, 2016)
Metarhizium anisopliae (Metsch.) Sorokin is one of the entomopathogenous fungi species which is widely used to control various insect pests in agriculture areas. This paper observes the effective isolates to control subterranean termites. Five isolates: PLT, SMG, PKM, BDG, and BGR were tested in the laboratory, while three isolates: SMG, PKM and BDG were tested on the field. Each isolate was mixed with sieved sand (60-80 mesh) in various concentration (v/v) of 0% (untreated), 10%, 20%, 50% and 100%. The results showed that based on the laboratory test, 10% concentration of BGR isolate was the most effective in controlling subterranean termites Coptotermes curvignathus Holmgren, and PLT was the most ineffective isolate. However, all isolates tested in the field were not effective against subterranean termites.